ANALYSIS OF THE CONFLICT OF TAXATION: EXPLORING MULTI-NATIONAL CORPORATIONS INCOME TAX CRITERIA IN INDONESIA - Butarbutar, Russel; Juwana, Hikmahanto; Sutratman, (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted qualitatively to resolve tax conflicts between Contracting States related to MNC taxes, which are usually carried out with tax approval and resolution related to company income, which is contained in a tax agreement. The goal is to find out the income tax criteria at the company. Qualitative research methods that describe the relationship between conflict and different Contracting States and will be used by multinational companies. The results of this study, found that tax agreements cannot be completed in accordance with existing provisions, due to several reasons. First, the tax problem between Contracting States, each of which has different political and tax objectives. Second, competition arises among Contracting States in fighting over the proportion of tax revenue from MNCs. Third, there is a tendency for MNCs to avoid taxes. Further research is needed to assess the effectiveness of tax agreements between Contracting States. In conclusion all the criteria related to MNC foreign capital taxation become clear which are stated in the overall agreement n the supervision of the tax and investment authority by the coordinating institution.